2013
DOI: 10.1016/j.gca.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the glycerol dialkyl glycerol tetraether temperature signal in speleothems

Abstract: Palaeotemperature proxies based on glycerol dialkyl glycerol tetraethers (GDGTs) lipids have been established for marine and lacustrine environments, but there has been relatively little study of their application in speleothems. In this study we analyse the GDGT content of 33 speleothem samples from 16 different sites around the globe, and test whether proxies based on isoprenoid tetraethers (TEX 86 ) or branched tetraethers (MBT/CBT) are correlated with measured surface and cave mean annual air temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…; Table S2b) for direct comparison with lake sediment data to confirm whether lakes and their catchment soils represent strongly connected habitats for brGDGT‐synthesizing bacteria or unique bacterial habitats with a separate temperature adaptation as already implied from comparison of GDGT compositions (see above). This is in line with several other studies that have demonstrated that there is a pressing need for individual calibrations for different terrestrial environments such as soils, lakes, rivers or caves (Weijers et al ., ; Tierney and Russell, ; Tierney et al ., ; Wang et al ., ; Blyth and Schouten, ; Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…; Table S2b) for direct comparison with lake sediment data to confirm whether lakes and their catchment soils represent strongly connected habitats for brGDGT‐synthesizing bacteria or unique bacterial habitats with a separate temperature adaptation as already implied from comparison of GDGT compositions (see above). This is in line with several other studies that have demonstrated that there is a pressing need for individual calibrations for different terrestrial environments such as soils, lakes, rivers or caves (Weijers et al ., ; Tierney and Russell, ; Tierney et al ., ; Wang et al ., ; Blyth and Schouten, ; Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Peterse et al, 2011;Huguet et al, 2012), stalagmites (e.g. Yang et al, 2011;Blyth and Schouten, 2013) and hot springs (e.g. Schouten et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since studies first demonstrated the presence of organic matter (OM) entrapped in calcite (Baker et al, 1996;Ramseyer et al, 1997), a number of organic components of speleothems being used as proxies for investigating changes in soils, vegetation, and climate (e.g., Baker et al, 1998;Blyth & Schouten 2013;Blyth et al 2011;Blyth et al, 2014;Bosle et al, 2014;Li et al, 2014;Perrette et al, 2005, Perrette et al, 2008Webb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%